Examining the Role of Hypothalamus-Derived Neuromedin-U (NMU) in Bone Remodeling of Rats - Gabriella Born-Evers; Ashley L. Orr; Elizabeth Q. Hulsey; Maria E. Squire; Julia M. Hum; Lilian Plotkin; Catherine Sampson; Jonathan Hommel; Jonathan W. Lowery (Life, 2023)
Global loss of the neuropeptide Neuromedin-U (NMU) is associated with increased bone formation and high bone mass in male and female mice by twelve weeks of age, suggesting that NMU suppresses osteoblast differentiation and/or activity in vivo. NMU is highly expressed in numerous anatomical locations including the skeleton and the hypothalamus. This raises the possibility that NMU exerts indirect effects on bone remodeling from an extra-skeletal location such as the brain. Thus, in the present study we used microinjection to deliver viruses carrying short-hairpin RNA designed to knockdown Nmu expression in the hypothalamus of 8-week-old male rats and evaluated the effects on bone mass in the peripheral skeleton. Quantitative RT-PCR confirmed approximately 92% knockdown of Nmu in the hypothalamus. However, after six weeks, micro computed tomography on tibiae from Nmu-knockdown rats demonstrated no significant change in trabecular or cortical bone mass as compared to controls. These findings are corroborated by histomorphometric analyses which indicate no differences in osteoblast or osteoclast parameters between controls and Nmu-knockdown samples. Collectively, these data suggest that hypothalamus-derived NMU does not regulate bone remodeling in the postnatal skeleton. Future studies are necessary to delineate the direct versus indirect effects of NMU on bone remodeling.